2020
DOI: 10.3389/fpls.2020.00495
|View full text |Cite
|
Sign up to set email alerts
|

Population Genomics and Phylogeography of a Clonal Bryophyte With Spatially Separated Sexes and Extreme Sex Ratios

Abstract: The southern Appalachian (SA) is one of the most biodiversity−rich areas in North America and has been considered a refugium for many disjunct plant species, from the last glacial period to the present. Our study focuses on the SA clonal hornwort, Nothoceros aenigmaticus J. C. Villarreal & K. D. McFarland. This hornwort was described from North Carolina and is widespread in the SA, growing on rocks near or submerged in streams in six and one watersheds of the Tennessee (TR) and Alabama (AR) Rivers, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 73 publications
1
9
0
Order By: Relevance
“…Despite some alternative processes that could also contribute to the tendency above (e.g., current climatic differences between long-and short-term persistent populations, or differences in their phylogeographic history), this result is remarkable and has been suggested for other bryophytes based on genetic data and considering the glacial periods of the Pleistocene (Alonso-García et al, 2020). Since our "young populations" have been potentially established since the LGM (from 19 000 years BP onwards), the persistence of such a historical signal suggests that shifts in sex ratios could operate at the scale of thousands of years (Cronberg, 2000;Alonso-García et al, 2020;Bisang et al, 2020;Blackstock, 2020). Recent evidence by Hedenäs et al (2021), supports the hypothesis of a gradual shift in population sex ratio from balanced toward skewed sex ratios.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Despite some alternative processes that could also contribute to the tendency above (e.g., current climatic differences between long-and short-term persistent populations, or differences in their phylogeographic history), this result is remarkable and has been suggested for other bryophytes based on genetic data and considering the glacial periods of the Pleistocene (Alonso-García et al, 2020). Since our "young populations" have been potentially established since the LGM (from 19 000 years BP onwards), the persistence of such a historical signal suggests that shifts in sex ratios could operate at the scale of thousands of years (Cronberg, 2000;Alonso-García et al, 2020;Bisang et al, 2020;Blackstock, 2020). Recent evidence by Hedenäs et al (2021), supports the hypothesis of a gradual shift in population sex ratio from balanced toward skewed sex ratios.…”
Section: Discussionmentioning
confidence: 92%
“…The rationale behind this approach is that populations resulting from postglacial recolonization were expected to be younger than populations in glacial refugia. Thus, we expected a highly skewed distribution of phenotypic sex ratio (i.e., a larger proportion of females) in glacial refugia due to the isolation and the concomitant longer period to accumulate the effects of any sex‐specific competitive advantage (i.e., sex‐specific differences in vegetative growth), than in areas that had been recolonized during the current interglacial period (Alonso‐García et al, 2020). Glacial refugia were estimated assuming that the current northern limit of the species distribution reflects its thermal limit.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In bryophytes, as observed herein for R. flaccida , asexual reproduction plays an important role in maintaining genetic diversity over time by preventing local genotype extinction and assuring successful sexual reproduction (Alvarenga et al, 2016). Evidence from unisexual bryophytes found that genetic diversity is maintained when species stakes on asexual reproduction for their survival (Pohjamo et al, 2008;Wang et al, 2013;Holá et al, 2015;Escolástico-Ortiz et al, 2023), but contrasting evidence was found for a hornwort species (Alonso-Garcia et al, 2020).…”
Section: Consequences Of Mating System and Dispersal Potentialmentioning
confidence: 87%